CAUSAL INFLUENCE STRUCTURE FOR SUSTAINABLE GROWTH OF SMALL AND MEDIUM ENTERPRISES IN THE SOUTHERN BORDER PROVINCES - Phetkaew , Chutikan; Phayoopun, Thammayantee (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to 1) examine the coherence of the hypothetical model with the empirical data on the causal influence structure for the sustainable growth of small and medium-sized enterprises in the southern border provinces. 2) study direct, indirect and total effect of factors affecting the causal influence structure. A questionnaire was used as a tool to collect data from 830 participants as samples via stratified sampling and simple random sampling. Data were analyzed using structural equation modeling techniques. The results showed that 1) the developed structural equation model was consistent with the empirical data (X2/df = 1.522, IFI = 0.975, NFI = 0.930, TLI = 0.973, CFI = 0.975, GFI = 0.910, AGFI = 0.902, and RMSEA = 0.025). Therefore, the theory can be applied to explain the relationship between variables and actual phenomena of small and medium-sized enterprises in the southern border provinces. 2) The external and internal environment have a direct influence on strategic management. It was statistically significant at 0.01 and strategic management had a direct influence on sustainable growth. It was statistically significant at 0.01 level, while the external and internal environment had an indirect influence on sustainable growth statistically significant at level 0. 01. The results of this study are beneficial to small and medium enterprises entrepreneurs. The entrepreneurs must keep up with the changes in the current environment by implementing strategic management processes in the organization. At the same time, the relevant departments should provide support that is conducive to the operations of small and medium-sized enterprises, so that small and medium-sized enterprises in the southern border provinces can survive and grow sustainably.